2018
DOI: 10.3390/pr7010010
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Advanced Functional Material Applications of Nanocellulose

Abstract: The need to transition to more sustainable and renewable technology has resulted in a focus on cellulose nanofibrils (CNFs) and nanocrystals (CNCs) as one of the materials of the future with potential for replacing currently used synthetic materials. Its abundance and bio-derived source make it attractive and sought after as well. CNFs and CNCs are naturally hydrophilic due to the abundance of -OH group on their surface which makes them an excellent recipient for applications in the medical industry. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
58
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 115 publications
(77 citation statements)
references
References 121 publications
1
58
0
Order By: Relevance
“…Nanocellulose fibrils, which are the building blocks of plant cell [95] walls and give plants and trees their structural strength and stiffness, are a very interesting and well-studied nanoscale natural material that can potentially improve the properties of the polymers [96]. Many studies have already reported on use of nanocellulose in different forms for composite applications [70].…”
Section: Nanocellulosementioning
confidence: 99%
See 1 more Smart Citation
“…Nanocellulose fibrils, which are the building blocks of plant cell [95] walls and give plants and trees their structural strength and stiffness, are a very interesting and well-studied nanoscale natural material that can potentially improve the properties of the polymers [96]. Many studies have already reported on use of nanocellulose in different forms for composite applications [70].…”
Section: Nanocellulosementioning
confidence: 99%
“…Many studies have already reported on use of nanocellulose in different forms for composite applications [70]. Cellulose nanomaterials are considered as a suitable solution to replace commonly used inorganic nanofillers [97] because they are widely available, renewable, and biodegradable [96]. Moreover, they possess unique valuable characteristics, such as a high specific strength, moduli (100-200 GPa), and specific surface area.…”
Section: Nanocellulosementioning
confidence: 99%
“…During testing, each sample was first held at 25 °C for 2 min before being heated up to 250 °C at 10 °C/min under N2. The Xc was then calculated using Equations (3) and 4:…”
Section: Degree Of Crystallinitymentioning
confidence: 99%
“…Natural fibers exhibit many excellent properties and are low-density materials, which probably lead to lightweight composites with a high specific strength and modulus. Natural fibers also offer significant cost advantages and easy processing along with being a highly biodegradable resource, as well as reducing the pollution to the environment [1][2][3]. Ramie fibers as one of the high-performance natural fibers [4] were selected and used in this work for the purpose of reinforcement of the resin.…”
Section: Introductionmentioning
confidence: 99%
“…Panchal et al [8] show that nanocellulose, in the form of cellulose nanocrystals and cellulose nanofibers, obtained by the deconstruction of fibers from wood or other cellulosic plants, are very appealing materials for functional material applications. This is because of their sustainability attributes, excellent mechanical properties owing to their crystalline assembly, and their abundant surface hydroxyl groups, which make them amenable to chemical modification.…”
mentioning
confidence: 99%